Pedotransfer functions for adsorbed phosphorus evaluations using magnetic susceptibility for mapping purposes - da Silva, Luis Fernando Vieira; Silva, Laércio Santos; de Bortoli Teixeira, Daniel; Siansi, Frederico Luiz [UNESP]; França, Ana Beatriz Coelho [UNESP]; Júnior, José Marques [UNESP] (Springer Nature, 2023)
This study evaluated the spatial variability of magnetic minerals and the potential of mass-specific magnetic susceptibility (χlf) to recognize minimum areas of phosphorus adsorbed (Pads). In an area of 443 ha cultivated with sugar cane in the state of São Paulo, 84 soil samples were collected at a depth range of 0.0–0.20 m. Analysis of mass-specific magnetic susceptibility at low (χlf) and high (χhf) frequencies was performed in all soil samples. Characterization of ferrimagnetic minerals was carried out by X-ray diffraction (XRD) and the chemical distinction between lithogenic (magnetite-Mt) and pedogenic (maghemite-Mh) ferrimagnetic minerals was determined by χlf before and after chemical reduction by citrate-bicarbonate-dithionite (CBD), with subsequent determination of Pads. The analytical results were evaluated by descriptive analysis and the spatial pattern was assessed by applying the geostatistical technique. χlf differentiated soils from their respective parent material even under conditions of high weathering and lithologic complexity. Positive linear correlations between Pads and clay (R2 = 0.77; p < 0.01), Pads and χlf (R2 = 0.86; p < 0.01), and Pads and Mh (R2 = 0.84; p < 0.01) indicated the use of χlf as a component of pedotransfer functions (PTF) for indirect quantification of Pads in the soil. Quantification of Mh and Mt by χlf was more sensitive than by XRD. The spatial pattern of ferrimagnetic minerals indicated that Mh originated from the direct oxidation of Mt. Soil χlf was sensitive to the spatial variability of Pads and might have assisted with the identification of minimum areas of phosphate fertilization in soils under lithologic complexes.
Keywords: Iron oxide; Maghemite; Magnetite; Magnetometer; Pedometrics; Spatial variability